Information feedback in a dynamic tournament - Masaki Aoyagi (Osaka University, Institute of Social and Economic Research (ISER), 2003)
This paper studies the problem of information revelation in a multi-stage tournament where the agents' effort in each stage gives rise to a stochastic performance signal privately observed by the principal. The principal controls the agents' effort incentive through the use of a feedback policy, which transforms his private information into a public announcement. The optimal feedback policy is one that maximizes the agents' expected effort. The paper identifies when the principal should use the no-feedback policy that reveals no information, or the full-feedback policy that reveals all his information.
Keywords: C72; D82; 330; tournament; mechanism; information revelation; Jensen's inequality; Prinzipal-Agent-Theorie; Leistungsanreiz; Signalling; Theorie